2015
DOI: 10.1016/j.ijgo.2015.03.045
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Third‐trimester uterine artery Doppler measurement and maternal postpartum outcome among patients with severe pre‐eclampsia

Abstract: Increased uterine artery resistance in the third trimester of pregnancy could be used to predict postpartum maternal complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…4 The frequency in multiparas is lower than that in nulliparas. 4 The diagnosis of pre-eclampsia is difficult. The symptoms include hypertension and signs of multiple organ disease.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…4 The frequency in multiparas is lower than that in nulliparas. 4 The diagnosis of pre-eclampsia is difficult. The symptoms include hypertension and signs of multiple organ disease.…”
Section: Introductionmentioning
confidence: 94%
“…The syndrome affects 2%–8% of pregnancies and remains a leading cause of perinatal mortality and morbidity worldwide . The prevalence of pre‐eclampsia in nulliparous populations ranges from 3% to 10% . The frequency in multiparas is lower than that in nulliparas …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Historically, the areas of health coverage and quantity of healthcare providers have been the focus of program implementation at the national level [ 10 ]. It has only been recently that the quality of care has received attention [ 7 ]. In recent years, however, more studies have reported on women’s experiences of disrespectful and abusive care during childbirth at facilities by healthcare providers.…”
Section: Introductionmentioning
confidence: 99%
“…Bowser and Hill (2010) systematically reviewed disrespect and abuse (D&A) by healthcare providers and categorized the various forms of abuse as physical abuse, non-consented care, non-confidential care, non-dignified care, discrimination, abandonment, and detention in facilities [ 4 ]. Moreover, these categories may overlap [ 4 , 7 ] and can occur along a continuum from subtle discrimination to overt violence [ 11 ]. In Tanzania, quantitative studies on midwifery have also revealed the negative care experiences of women.…”
Section: Introductionmentioning
confidence: 99%